Influence Endogeneity And Embeddedness Dimensions Of Integrated Rural Tourism Program On Community Well-Being Of Lake Toba North Sumatera, Indonesia - Sulthony, Zumri; Lubis, Suwardi; Purwoko, Agus; Tarmizi, H.B. (International Journal of Educational Research & Social Sciences, 2023)
Lake Toba area has been designated as a national strategic area and national tourism object. Therefore, development of its surrounding areas become a priority for government. Since Lake Toba is surrounded by many villages, it is suggest that development of this area was done through integrated rural tourism program. This research was done to find out the influence of endogeneity and embeddedness in integrated rural tourism program on community well-being of Lake Toba. The research was held from July to Desember 2021. The survey was conducted to 240 people from 8 regencies surrounding Lake Toba: Samosir, Toba, Simalungun, North Tapanuli, Humbang Hasundutan, Dairi, Karo and West Pakpak Regencies. The sample consists of the community, entrepreneurs, policy makers, academics, and stakeholders. Data of community well-being, endogenous and embeddedness aspects of integrated rural tourism was analyzing using multiple regression analysis. The results shows that endogenous and embeddedness aspects of integrated rural tourism partially and simultaneously influence community well-being.